Managing Cyber-Security of in-Bank Ecosystem in Conditions of Digitalization - A. D. Bezdelov; E. V. Loginova (Вестник Российского экономического университета имени Г. В. Плеханова)
Information technologies (IT) play a key role in corporate infrastructure. They provide unprecedented economic development of enterprises in our era. IT systems help economize resources and give an opportunity to peep in the essence of corporate transactions. Finance service market develops energetically due to digital economy shaping. Digital technologies have penetrated all spheres of life and the level of innovation technology equipment keeps on growing at the expense of mobile technologies. The system of in-company finance control is included n the structure of management functioning as an obligatory element of the current mechanism of management. The development of programs of in-bank control is a necessary component of work of any finance and credit organization according to international and national legislation. The article describes the structure of unique in-bank mechanism of control, oriented to preventing legalization of criminal incomes and raining personnel for services of internal bank control. The article analyzes in-bank programs aimed at its organization and grounds functional responsibilities of employees in divisions of internal control integrated in the system of monitoring and managing bank risks. The role of questionnaires differentiated by clients’ types is assessed, with the help of which the bank can identify its clients. Programs of training employees of internal control divisions are structured.